"Seja o que Deus quiser. Eu escrevi a realidade." Carolina Maria de Jesus e o registro da experiência social dos trabalhadores pobres no Brasil (1920-1970) - Noal, Sara Munique (2019)
The History from below consolidated itself as a fertile field of studies that sought and seek to produce a narrative that privileges the analysis of society having as a prism the experience of subaltern groups. This task is not simple, bearing in mind that such groups, due to the social condition they occupy in society, do not have the necessary means and instruments to record their history. Finding written records by workers who synthesize their ways of seeing and feeling in the world is relatively rare. From this point of view, having access to the writings of Carolina Maria de Jesus is almost a privilege for any researcher interested in knowing and analyzing the lives of Brazilian workers. In her diaries, novels, poems, proverbs and other writings, we find a narrative strongly impregnated by objective and subjective elements of the life of a Brazilian woman, black and poor, between the years of 1920 and 1970. At the same time, her texts allow us to approach also of the daily life of the workers, because their field of reflection was always directed to the world that surrounded it. Through his work it is possible to access and analyze questions about workers' culture, their ideas and their way of life. More than that, these questions appear through the reports of a worker who dared to challenge her social place of origin, demonstrating the difficulties faced by workers to enter and remain in the intellectual universe.